Analysis of Factors Affecting Sheep Production at Dompet Dhuafaâ€™s Livestock Center in Deli Serdang District - Harahap, Wirda Murlan; Siregar, Galih Ari Wirawan; R. Edhy Mirwandhono (Jurnal Peternakan Integratif, 2024)
Dompet dhuafa is the largest sheep center in Deli Serdang District. Some of the factors that affect sheep farming production are area, livestock, labor, and cost. The aim of the study was to analyze the effect of the number of livestock, housing capacity, labor, feed, seed sources, and health on fattening sheep production in the study area. The sampling technique consisted of primary data and secondary data. The collection was done by interview technique using questionnaire data. The data analysis method used is multiple linear regression and SWOT analysis. The results of the study that there was an influence the number of livestock (X1), cage capacity (X2), feed (X4) and health (X6) on fattening sheep production (Y), while for the variables, labor (X3) and seed sources (X5) did not influence the production of fattening sheep (Y) in the study area. The results of the swot analysis on the development strategy or aggressive strategyÂ  consistsed of 4 strategies of 1. Making Dompet Dhuafa a producer of sheep, 2. Developing human resources for productive breeders, 3. Establishing continuous cooperation with agents and consumers, 4. Increase the number of sheep population. In conclusion that various factors influence productivity, which helps in understanding and optimizing these factors to improve the efficiency and productivity of sheep production in the Dompet Dhuafa.